Moderation of Couples in Inter-Economic Marriages in the Modern Era - Muhammad Elvandriyani Yusup; Nazwa Adibah Suherman; Arini Rizqina (Lembaga Yasin AlSys, 2026)
Inter-economic marriages, characterized by pronounced disparities in income, education, occupation, or assets between spouses, pose unique challenges to household harmony in contemporary Indonesia. This study examines the lived experiences of such couples, their adaptation strategies, and Islamic scholarly perspectives on compatibility (kafa’ah) and maintenance (nafkah). Employing an interpretive phenomenological approach, data were collected through in-depth interviews and participant observation with purposively selected husband–wife pairs married for at least two years, analyzed using thematic content analysis and hermeneutic interpretation, and triangulated with classical fiqh texts and contemporary fatwas. The findings reveal that open communication, self-disclosure, and family resilience mitigate conflicts arising from economic disparities, fostering emotional bonds and mutual empathy despite external pressures such as Long Distance Marriage (LDM). From an Islamic legal perspective, nafkah extends beyond minimal provisions (food, clothing, and shelter) to contextually appropriate support (ma’ruf), as reflected in Q.S. Al-Baqarah/2:233, while kafa’ah harta emphasized to varying degrees across Hanafi, Maliki, Shafi’i, and Hanbali madhhabs—ultimately prioritizes religious piety over wealth to prevent discord. The study concludes that couples in inter-economic marriages can achieve sakinah, mawaddah, and rahmah by aligning their roles flexibly and upholding shari’ah-guided equity, demonstrating that economic disparities need not undermine marital stability when countered with proactive adaptation, and offering insights for premarital counseling in diverse Muslim societies.